AIDS: the new challenge to food security: IFPRI 2001-2002 Annual Report Essay - Piot, Peter; Pinstrup-Andersen, Per (International Food Policy Research Institute, 2002)
It is easy to forget in the complicated world of global AIDS politics that for many people around the world, AIDS is one additional burden on top of many others. AIDS does not occur in a vacuum. People’s basic concerns remain the same as they have always been: a secure, decent livelihood for themselves and their families. In Africa, where the pandemic is currently the most serious, AIDS emerged against a backdrop of extreme poverty, hunger, conflict, and inadequate infrastructure. The impact of AIDS has been to make preexisting problems and their consequences far worse, and to create daunting new problems. By killing people in the prime of their lives, when they would normally be raising their children and practicing their professions, AIDS erodes the social capital that makes communities function. AIDS has decimated the very generation of young adults poised to take Africa’s future into their own hands.